Daylighting Performance of Various Layout Alternatives in an Open Building Apartment in Surabaya - Hendrik, M.L.; Dinapradipta, Asri; Ekasiwi, Sri Nastiti N. (IPTEK Journal of Proceedings Series, 2018)
Utilization of natural light in an open building apartment is one of the several ways to save energy. Not only saving energy but it also sustains the healthy life of the occupants. This paper discusses the effect of layout alternatives mainly due to the potential changing arrangement of the bedrooms and the position of transparent window surfaces on daylighting performance i.e illuminance distribution and averages of illuminance. The Method used in this paper is an experimental method using Radiance 1.02 simulation as a tool. The changed layout in which is the bedroom spaces position concentrated on one window side of space with two separated transparent windows provides a good result with a percentage of area fulfills the standards equals to 29%